Vectorial capacity of Aedes aegypti for dengue virus type 2 is reduced with co-infection of Metarhizium anisopliae. - Javier A Garza-Hernández; Mario A Rodríguez-Pérez; Ma Isabel Salazar; Tanya L Russell; Monsuru A Adeleke; Erik de J de Luna-Santillana; Filiberto Reyes-Villanueva (PLoS Neglected Tropical Diseases, 2013)
Background Aedes aegypti, is the major dengue vector and a worldwide public health threat combated basically by chemical insecticides. In this study, the vectorial competence of Ae. aegypti co-infected with a mildly virulent Metarhizium anisopliae and fed with blood infected with the DENV-2 virus, was examined. Methodology/principal findings The study encompassed three bioassays (B). In B1 the median lethal time (LT50) of Ae. aegypti exposed to M. anisopliae was determined in four treatments: co-infected (CI), single-fungus infection (SF), single-virus infection (SV) and control (C). In B2, the mortality and viral infection rate in midgut and in head were registered in fifty females of CI and in SV. In B3, the same treatments as in B1 but with females separated individually were tested to evaluate the effect on fecundity and gonotrophic cycle length. Survival in CI and SF females was 70% shorter than the one of those in SV and control. Overall viral infection rate in CI and SV were 76 and 84% but the mortality at day six post-infection was 78% (54% infected) and 6% respectively. Survivors with virus in head at day seven post-infection were 12 and 64% in both CI and SV mosquitoes. Fecundity and gonotrophic cycle length were reduced in 52 and 40% in CI compared to the ones in control. Conclusion/significance Fungus-induced mortality for the CI group was 78%. Of the survivors, 12% (6/50) could potentially transmit DENV-2, as opposed to 64% (32/50) of the SV group, meaning a 5-fold reduction in the number of infective mosquitoes. This is the first report on a fungus that reduces the vectorial capacity of Ae. aegypti infected with the DENV-2 virus.